Healthcare and telehealth use among U.S. immigrants during the COVID-19 pandemic - Merianne Rose T. Spencer; Sunjung Yoon; Youngeun Lee; Arturo Vargas Bustamante; Jie Chen; Jie Chen (Frontiers Media S.A., 2024)
IntroductionRecent studies have documented the negative impact of the COVID-19 pandemic on low-income families, rural and underserved areas, and racial and ethnic minority populations. However, less is known about immigrants' healthcare access and utilization, including telehealth use. This study investigated disparities in healthcare access and utilization by immigration status among adults aged 18-64 years during the COVID-19 pandemic.MethodsThis cross-sectional study pooled data from the 2020 and 2021 National Health Interview Survey (NHIS). Multivariable logistic regression models were used to estimate the variation of healthcare access and utilization by citizenship and nativity status. Immigration status (U.S.-born citizen, naturalized U.S. citizen, and non-citizen) served as the key independent variable. Healthcare access measures were dichotomized indicators of whether individuals had delayed medical care either due to cost or due to COVID-19. Healthcare utilization measures included whether individuals visited a doctor, used the emergency room, or had a telehealth visit during COVID-19.ResultsCompared to U.S.-born citizens, non-citizen immigrants were more likely to delay medical care due to cost (adjusted OR = 1.375, [95%CI: 1.137, 1.662]), less likely to visit a doctor (adjusted OR = 0.71, [95%CI: 0.617, 0.817]), or visit an emergency room (adjusted OR = 0.756, [95%CI: 0.635, 0.901]). Non-citizen immigrants were less likely to have a telehealth visit (either video or phone visits) during COVID-19 (adjusted OR = 0.634, [95%CI: 0.557, 0.723]).DiscussionCompared to U.S.-born citizens, lower healthcare and telehealth utilization persisted among non-citizen immigrants during the pandemic.